2017
DOI: 10.1155/2017/5612843
|View full text |Cite
|
Sign up to set email alerts
|

Currency and Competence of Occupational Therapists and Consumers with Rapidly Changing Technology

Abstract: Assistive technology was once a specialised field of practice, involving products designed for populations with specific impairments or functional goals. In Australia, occupational therapists have, at times, functioned as gatekeepers to public funding, prescribing products from a predefined list. An expanding range of accessible mainstream products available via international and online markets has changed the meaning and application of assistive technology for many people with disability. In the policy contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
(20 reference statements)
2
11
0
Order By: Relevance
“…However, this study showed that SOs sometimes requested advanced time AT, or wanted to use functions in smart phones, that the OTs considered to be too difficult to use for PwDs. This is in line with earlier research that has found that smart phones, with comparable supportive functions, often can be too advanced for PwDs [31,48].…”
Section: Discussionsupporting
confidence: 91%
“…However, this study showed that SOs sometimes requested advanced time AT, or wanted to use functions in smart phones, that the OTs considered to be too difficult to use for PwDs. This is in line with earlier research that has found that smart phones, with comparable supportive functions, often can be too advanced for PwDs [31,48].…”
Section: Discussionsupporting
confidence: 91%
“…As some individuals were resistant to help, training would need to be provided in a sensitive and optional format. The importance of ongoing training, assessment and support are commonly emphasised within the area of assistive technologies in order to reduce barriers to use (Steel et al, 2017, Jamwal et al, 2020, Adolfsson et al, 2016Boot et al, 2018). Our study sits well within this past work and stresses the importance of developing accessible and adaptive training and support for users.…”
Section: Training Support and Future Directionssupporting
confidence: 75%
“…Despite high levels of excitement about the use of technology in rehabilitation [12], actual knowledge about devices and technological solutions has been limited for not only the elderly, but also for most people with disabilities [6]. Self-efficacy has been posited as an important factor, as those with high levels of self-efficacy are more likely to engage in rehabilitation and to be early adopters of new technologies [13].…”
Section: The Technology Challenge In Rehabilitationmentioning
confidence: 99%